ANALISIS KARAKTERISTIK PASIEN DIABETES MELITUS DAN KADAR HbA1C SEBAGAI FAKTOR RISIKO KEJADIAN NEUROPATI DIABETIK - Henky, Jefri; Tusaddyah, Aisyah (Nusantara Hasana Journal, 2025)
Diabetes Mellitus is a disease characterized by increased blood sugar levels. Indonesia is ranked 5th in the world with the highest number of diabetes mellitus sufferers. Diabetic neuropathy is a chronic complication in patients with type 2 diabetes mellitus. The risk factors that cause diabetic neuropathy are divided into two, namely factors that can be modified hyperglycemia, hypertension, dyslipidemia, obesity, and alcohol consumption, and risk factors that cannot be modified age, gender, duration of suffering from DM, and HbA1C levels. This research is observational analytic using a case control design, to determine the characteristics of diabetes mellitus patients and HbA1C levels as risk factors for diabetic neuropathy. The sample in this study was selected using a consecutive sampling technique and the number of samples in this study was 31 samples in the case group and 31 samples in the control group. The highest age of patients in this study was in the group ≥60 years, namely 17 patients (54.8%), the risk factor was that age ≥60 years in diabetes mellitus patients had a 1.3 times chance of suffering from diabetic neuropathy (OR=1.304; 95% CI = 0.474-3.585). The largest gender was in the female group, namely 21 patients (67.7%), risk factors: female gender has a 1.1 times chance of suffering from diabetic neuropathy (OR=1.164; 95% CI= 0.395-3.431). The highest BMI was in the normal group, namely 19 patients (61.3%), in this study BMI was not a risk factor for diabetic neuropathy (OR=1.000; 95% CI=0.360-2.779). The longest duration of suffering from DM was in the >5 years group, namely 17 patients (54.8%), the risk factor was that the duration of suffering from DM >5 years was 1.7 times the chance of suffering from diabetic neuropathy (OR=1.729; 95% CI=0.615-4.860). The smoking habit was highest in the non-smoking group, namely 20 patients (64.5%), in this study smoking habit was not a risk factor for diabetic neuropathy (OR=1,000; 95% CI=0.353-2.831). The highest HbA1C levels in this study were in the uncontrolled group, namely 17 patients (54.8%), risk factors for uncontrolled HbA1C had a 1.1 times chance of suffering from diabetic neuropathy (OR=1.140; 95% CI=0.418-3.114). Age, gender, duration of suffering from DM and HbA1C levels are risk factors for diabetic neuropathy.